The Development of International Tourists During The Pandemic: The Perception of Local Tourists - Ratu Noorita Achmad; Muhammad Arifin Muhammad Salim; Amirullah (Politeknik Pariwisata Makassar, Indonesia, 2022)
The Covid-19 pandemic has hampered various kinds of activities, especially in the world of tourism. Based on data on international tourist visits to Indonesia in August, it experienced a significant decrease of 89.22%. The Deputy for Destination and Infrastructure Development of the Ministry of Tourism and Creative Economy (Kemenparekraf) predicts that international tourist visits to Indonesia only occupy the number 4 million people, which before the pandemic occupied the figure of 18 million visitors. The purpose of this study is to find out the perception of local tourists towards the development of international tourists during the pandemic, the method used is to conduct interviews with local tourists randomly in the Barru district. The analysis method used is descriptive qualitative to explain the research results obtained. The result of this study is that the decline in tourism visitors has a significant impact on people's income, especially in Barru district, but this, it can reduce the spread of the Covid-19 virus that is sweeping the world.